Peningkatan Pengetahuan Kesehatan Gigi dan Mulut di SDN Margomulyo 1 - Utari, Tita Ratya; Aurelia Calula Syahnaz Efendi; Keisha Zulfira; Muhammad Nur Anifan; Nadia Nur Utaminingsih; Nikita Salma Maulida; Neva Valencia Eka Apriliana; Sadhewa Chandra Ardhi Nugroho (Dental Agromedis, 2024)
Good oral and dental health status in children is very important for children's growth, development, health and welfare. Oral hygiene is one of the important standards for maintaining good dental and oral health. Based on 2018 Basic Health Research (Riskesdas) data, the majority of people (94.7%) currently have the habit of brushing their teeth every day, but only 2.8% brush their teeth properly. SDN Margomulyo 1 is one of the elementary schools in Sleman, Yogyakarta where the majority of students generally have the habit of snacking and sweet foods without following the habit of maintaining good dental and oral health. This community service is carried out by holding dental health education and tooth brushing training for students in grades 4 and 5. All students do questions before and after the education to determine the level of students' knowledge. The results of statistical analysis using the Wilcoxon test obtained p <0.05 which shows that there is a significant difference before and after the counseling, so it can be concluded that counseling about dental and oral health and tooth brushing training is effective in increasing the knowledge of grade 4 and 5 of elementary school students at SD N Margomulyo 1.Keywords: counseling, oral health, training, brushing teeth